Forget SQL for a moment: Build Your First Database with MongoDB - Rafiyandi, Danu Sisda; Algibran, Kevin Raydafa; Saputra, Muhammad Fikri Dwi; Yatin Nafiah, Nandhita Ghin; Dahshal Alhareth, Naji Salem Ali; Meilina, Popy; Mujiastuti, Rully; Adharani, Yana; Rosanti, Nurvelly (Society : Jurnal Pengabdian Masyarakat, 2026)
The webinar and workshop “Forget SQL for a moment: Build Your First Database with MongoDB,” held on January 10, 2026, aims to provide knowledge about the NoSQL database service called MongoDB, with a focus on teaching how to install MongoDB, providing examples of terminal-based queries on Mongo Shell, and visualizing documents in the database using Mongo Compass. Additionally, participants learned how to install the MongoDB database server, access the database via the Mongo Shell terminal, and use Mongo Compass as a Graphical User Interface (GUI) to easily view document visualizations in each database collection. This event successfully attracted 35 student participants from the same department across all grades. This enthusiasm was also supported by the relevance of the course and the participants' interest in learning about the MongoDB database. The results of the pre-test, which participants took before the material was discussed, had an average score of 60.21 points and a median of 90 points, while the post-test, which participants took after the material was discussed in the webinar and workshop, had an average score of 71.88 points and a median of 100 points. In addition, participants provided mostly positive feedback, expressing enthusiasm and satisfaction with the event, as well as suggestions for improvement in the future. This activity served as a means of technological education that provided insight and supported the development of science and technology.